A composite polymer porous membrane and its preparation method and application

By designing specific solvents and removal methods to prepare composite polymer porous membranes, the existing membranes have low mass transfer efficiency and poor air isolation effect have been solved, and efficient and low-cost electrolytic hydrogen production technology is achieved, which is suitable for industrial production.

CN117385413BActive Publication Date: 2025-03-11TIANJIN POLYTECHNIC UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311324176.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-13
Publication Date
2025-03-11
Estimated Expiration
2043-10-13

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, the separator has low mass transfer efficiency, poor air isolation effect, insufficient mechanical and mechanical properties, high resistance, complex process and high cost, making it difficult to meet the needs of industrial production.

Method used

A specific first solvent and a second solvent are used to design the cast film liquid, and a composite polymer porous membrane is prepared by removing these two solvents in stages to form a three-dimensional penetration structure with a dense small pore diameter upper surface and an open large pore diameter lower surface.

Benefits of technology

It achieves high mass transfer efficiency, good gas isolation effect, excellent mechanical and mechanical properties and low resistance, meets the performance requirements of alkaline water electrolytic cells for the membrane, reduces system energy consumption and improves gas purity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117385413B_ABST
    Figure CN117385413B_ABST
Patent Text Reader

Abstract

The present invention provides a composite polymer porous membrane and a preparation method and application thereof, the preparation method comprising: mixing a first solvent, a second solvent, a polymer and hydrophilic inorganic particles to obtain a casting solution; the first solvent is a good solvent for the polymer, the boiling point of the first solvent is less than the boiling point of the second solvent, and the surface tension of the first solvent is less than the surface tension of the second solvent; the casting solution is coated on a support net to obtain a liquid film containing the support net; removing the first solvent in the liquid film to obtain a primary film; removing the second solvent in the primary film to obtain the composite polymer porous membrane. The preparation method is simple and easy to implement, and through the design and mutual compounding of the first solvent, the second solvent and a specific preparation process, a three-dimensional through structure with high porosity is formed in the obtained composite polymer porous membrane, which has the characteristics of high mass transfer efficiency, good gas isolation effect, high mechanical properties and low resistance, and fully meets the performance requirements of the alkaline water electrolyzer for the diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane materials, and in particular relates to a composite polymer porous membrane and a preparation method and application thereof. Background Art

[0002] Energy, as an important driving force for the progress of human society, plays a pivotal role. For a long time, people have been using traditional fossil energy as the main energy source, which has also brought some serious problems. On the one hand, traditional fossil energy, as a non-renewable resource, cannot meet the sustainable development of human society; on the other hand, excessive use of fossil fuels leads to the emission of greenhouse gases, which has a relatively bad impact on the global ecological environment. Therefore, it has become a consensus among countries around the world to develop clean and efficient renewable energy technologies and achieve sustainable development of mankind. Energy transformation is an inevitable choice for achieving sustainable economic and social development. Hydrogen energy is regarded as the best energy carrier for its advantages of cleanliness, high efficiency, easy storage and transportation. In addition to being used as energy, it is also widely used in many fields such as electronics and chemical industry, and the demand is increasing.

[0003] Among the many hydrogen production methods, water electrolysis is considered to be an efficient, large-scale, and clean hydrogen production technology. When two electrodes (cathode and anode) with direct current are immersed in an electrolyte, water will be decomposed and hydrogen and oxygen will be produced at the cathode and anode respectively. This process is called water electrolysis, and such a device is called an electrolyzer. In the traditional alkaline aqueous solution electrolysis process, asbestos cloth or polyphenylene sulfide (PPS) cloth is usually used as a diaphragm to isolate the electrodes and conduct the hydroxide (OH - ) is connected to the internal circuit. Since the pore size of the asbestos cloth or polyphenylene sulfide (PPS) used for isolation is large, in order to avoid the potential safety hazards caused by the mixing of the generated hydrogen and oxygen, the industry has strict restrictions on the pressure difference between the cathode and anode chambers. In addition, the hydrophilicity of asbestos cloth and polyphenylene sulfide cloth is poor, and the resistance in the tank is large, so the system consumes a lot of energy, resulting in excessively high electrolysis costs.

[0004] Improving the diaphragm is one of the main methods to optimize the electrolytic water hydrogen production technology. For example, polyphenylene sulfide is hydrophilically modified to improve its alkali absorption rate and conductivity. The commonly used hydrophilic modification method is to perform high-temperature sulfonation treatment in 98%-99% concentrated sulfuric acid to obtain sulfonated polyphenylene sulfide. Although the sulfonated polyphenylene sulfide has strong hydrophilicity, high-concentration sulfuric acid and high-temperature treatment are not conducive to industrial production and bring about thorny environmental problems. CN115029732A discloses a diaphragm for alkaline water electrolysis, which is made of organic polymer resin, porogen, inorganic nanoparticles and a support. The preparation process of the diaphragm is a traditional immersion precipitation method, which mainly utilizes the different solubility of polymers in solvents and non-solvents (coagulation baths). The solvent-non-solvent exchange rate is the most important factor determining the final membrane pore structure. Rapid solvent-nonsolvent exchange causes cortical rupture through creep relaxation of the polymer, thereby allowing for faster solvent-nonsolvent exchange under the ruptured cortical layer. More droplets of the lean phase will form and aggregate, resulting in large voids, which will give the diaphragm a large through-going finger-like pore structure and give it good wettability. However, the mechanical strength of asymmetric diaphragms with finger-like pores is generally poor, and their low porosity results in poor diffusion of the electrolyte within the membrane. In addition, the large amount of inorganic nanoparticles used results in a high raw material cost. Moreover, the interaction between the polymer and the inorganic nanoparticles is low, resulting in a relatively serious powdering problem during use, which results in the diaphragm being unable to meet the performance requirements for hydrogen production by electrolysis of water.

[0005] Therefore, it is an urgent problem to be solved in this field to develop a diaphragm material with high mass transfer efficiency, good gas isolation effect, good mechanical properties, low resistance, simple process, low cost, and suitable for industrial production to meet the needs of hydrogen production by electrolysis of water. Summary of the invention

[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a composite polymer porous membrane and a preparation method and application thereof. The preparation method is simple and easy. Through the design and mutual compounding of a first solvent, a second solvent and a specific preparation process, a three-dimensional through-structure with high porosity is formed in the obtained composite polymer porous membrane. The membrane has the characteristics of high mass transfer efficiency, good gas isolation effect, high mechanical properties and low resistance, which fully meets the performance requirements of the alkaline water electrolyzer for the diaphragm.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a composite polymer porous membrane, the preparation method comprising:

[0009] Mixing a first solvent, a second solvent, a polymer and hydrophilic inorganic particles to obtain a casting solution;

[0010] The first solvent is a good solvent for the polymer, and the second solvent is miscible with the first solvent; the boiling point of the first solvent is less than the boiling point of the second solvent, and the surface tension of the first solvent is less than the surface tension of the second solvent;

[0011] Applying the casting liquid on a support mesh to obtain a liquid film including the support mesh;

[0012] removing the first solvent in the liquid film to obtain a primary film;

[0013] The second solvent in the primary membrane is removed to obtain the composite polymer porous membrane.

[0014] In the preparation method provided by the present invention, a specific first solvent, a second solvent, a polymer and hydrophilic inorganic particles are firstly used to prepare a casting solution, and after the casting solution is coated on a support net to form a liquid film, the first solvent and the second solvent are removed in sections to obtain a composite polymer porous membrane; the specific concept is as follows:

[0015] (1) The first solvent is a good solvent for the polymer, so that the polymer can be fully dissolved to form a casting liquid; at the same time, the second solvent has good compatibility with the first solvent, so that the second solvent can be evenly distributed in the casting liquid and the liquid film, avoiding polymer precipitation, and forming a uniform porous structure in the composite polymer porous membrane.

[0016] (2) The boiling point of the first solvent is less than the boiling point of the second solvent, thereby achieving step-by-step removal of the first solvent and the second solvent; during the removal of the first solvent with a low boiling point, the second solvent can be retained in the membrane, and the formed primary membrane includes a support network, a polymer, hydrophilic inorganic particles and a second solvent.

[0017] (3) The surface tension of the first solvent is less than the surface tension of the second solvent. The surface tension difference formed makes it possible for most of the polymer in the casting solution to still interact with the second solvent during the removal of the first solvent, so that the formed primary film has the ability of secondary molding.

[0018] (4) In the process of removing the first solvent in the liquid film, when the evaporation of the first solvent reaches a certain extent, a thermodynamically unstable system is formed in the liquid film (casting liquid), resulting in phase separation of the liquid film to form a polymer-rich phase and a polymer-poor phase, wherein the polymer-poor phase contains a large amount of the second solvent. Since the second solvent has a high boiling point and is more difficult to evaporate than the first solvent, when the first solvent is completely evaporated and removed, the polymer segments begin to arrange and form a completely interconnected network with the second solvent. Since the second solvent has a strong hygroscopicity, it is easy to phase separate from the coagulation bath during the second solvent removal stage, forming a completely through three-dimensional pore structure. This structure is conducive to improving mass transfer efficiency, promoting diffusion and conduction of the electrolyte in the membrane, improving conductivity, and reducing resistance.

[0019] At the same time, in the stage of removing the first solvent in the liquid film, the polymer concentration in the surface layer increases to form a dense upper surface, and the surface tension of the second solvent is relatively large. When the first solvent is removed, the second solvent still interacts with most of the polymer due to its higher surface tension, so that the dense cortex formed by the first solvent is very thin, and the dense upper surface (cortex) hinders the diffusion of the second solvent; as the upper surface of the casting liquid (primary membrane) gradually solidifies, the second solvent inside will diffuse through the bottom surface, and the lean phase will gather at the bottom to form large pores; thus, the composite polymer porous membrane has an upper surface with a dense small-pore thin cortex and an open large-pore lower surface. The upper surface of the thin cortex can effectively avoid gas cross-talk, and the lower surface with open pores makes the composite polymer porous membrane have good electrolyte wettability.

[0020] (5) The casting solution contains hydrophilic inorganic particles, thereby forming a composite polymer porous membrane containing hydrophilic inorganic particles, which can regulate the structure of the membrane and the distribution of pores, effectively increase the hydrophilicity of the composite polymer porous membrane, promote the infiltration of the electrolyte into the membrane, and reduce the resistance. At the same time, since the composite polymer porous membrane has a high porosity and a high specific surface area, the hydrophilic inorganic particles are evenly loaded and are not easy to fall off. Under the premise of ensuring the hydrophilic property, the amount of hydrophilic inorganic particles added can be reduced, which greatly reduces the cost.

[0021] Therefore, the preparation method provided by the present invention is simple and easy to implement. Through the design and mutual coordination of the first solvent, the second solvent and the specific process steps, a composite polymer porous membrane with excellent comprehensive performance can be obtained quickly and rapidly. The composite polymer porous membrane has a dense thin skin layer, a three-dimensional through structure, a high porosity, a large specific surface area, good hydrophilicity and electrolyte wettability, and has the characteristics of high mass transfer efficiency, good gas isolation effect, high mechanical properties, and low resistance, which can fully meet the performance requirements of alkaline water electrolyzer diaphragms. The preparation method is simple and environmentally friendly, the membrane making process is easy to adjust, and the precise control of the membrane structure can be achieved, which is suitable for large-scale industrial production.

[0022] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0023] Preferably, the polymer includes any one of polysulfone, polyethersulfone, polyetheretherketone, polytetrafluoroethylene, polyphenylsulfone, polybenzimidazole, chitosan or a combination of at least two thereof. The polymer has the advantages of being resistant to alkaline corrosion and having high mechanical strength, and can especially meet the performance requirements of the alkaline water electrolysis process for the diaphragm.

[0024] Preferably, the boiling point of the first solvent is T1, the boiling point of the second solvent is T2, T2-T1≥40°C, for example, the difference between the two can be 42°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C or 170°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 45-165°C is further preferred.

[0025] As a preferred technical solution of the present invention, the boiling point of the second solvent is at least 40°C higher than that of the first solvent, and more preferably 45-165°C. Thus, it can be ensured that when the first solvent is removed by a drying method, the second solvent does not volatilize / evaporate, thereby forming a primary film containing the second solvent.

[0026] Preferably, the boiling point T1 of the first solvent is ≤170°C, for example, it can be 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or 160°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 40-165°C is further preferred.

[0027] Preferably, the surface tension of the first solvent is R1, the surface tension of the second solvent is R2, R2-R1≥5dyne / cm, for example, the difference between the two can be 5dyne / cm, 5.5dyne / cm, 6dyne / cm, 6.5dyne / cm, 7dyne / cm, 7.5dyne / cm, 8dyne / cm, 8.5dyne / cm, 9dyne / cm, 9.5dyne / cm, 10dyne / cm or 10.5dyne / cm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 5-10.5dyne / cm is further preferred.

[0028] Preferably, the first solvent includes any one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, toluene, dichloromethane, dioxane, acetonitrile, n-pentane, and n-hexane, or a combination of at least two thereof.

[0029] As a preferred technical solution of the present invention, the first solvent of a specific type is a good solvent for the polymer, that is, the difference in solubility parameter δ between the polymer and the first solvent is ≤0.5, so that the polymer is fully dissolved, and the presence of undissolved polymer clusters in the casting solution can be prevented. If there are undissolved polymer clusters in the casting solution, the undissolved polymer clusters will aggregate into crystal nuclei during the phase separation of the liquid film (casting solution), and the interaction force between the crystal nuclei is relatively small, so that the mechanical properties of the composite polymer porous membrane are poor. The first solvent with good solubility is conducive to the preparation of a composite polymer porous membrane with better mechanical properties.

[0030] Preferably, the second solvent is easily soluble in water and / or alcohol solvents; thus, the primary film can be secondary molded in a solvent bath (a solvent bath of water and / or alcohol solvent) and removed by solvent replacement.

[0031] Preferably, the boiling point of the second solvent is ≥180°C, for example, it can be 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 190-290°C is further preferred.

[0032] Preferably, the second solvent includes any one of N-methylpyrrolidone, sulfolane, ethylene glycol, triethyl phosphate, trimethyl phosphate, glycerol, and dibutyl phthalate, or a combination of at least two thereof.

[0033] As a preferred technical solution of the present invention, the type of the second solvent is as described above, which not only has a specific boiling point difference and surface tension difference with the first solvent, but also has excellent compatibility with the solvent in the subsequent solvent bath, and can maintain a suitable exchange rate, so that the obtained composite polymer porous membrane has a higher porosity and an ideal pore size structure.

[0034] Preferably, taking the total mass of the first solvent and the second solvent as 100%, the mass of the first solvent is 50%-90%, for example, it can be 55%, 60%, 65%, 70%, 75%, 80% or 85%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0035] That is, taking the total mass of the first solvent and the second solvent as 100%, the mass of the second solvent is 10%-50%, for example, it can be 15%, 20%, 25%, 30%, 35%, 40% or 45%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0036] As a preferred technical solution of the present invention, the first solvent in the liquid film is first removed by a drying method, and then the second solvent in the primary film is removed by a solvent replacement method in a solvent bath. When the first solvent is removed (evaporated / volatilized) to a certain extent, the liquid film (casting liquid) forms a thermodynamically unstable system, causing the casting liquid to undergo phase separation to form a polymer-rich phase and a polymer-poor phase. The second solvent has a higher boiling point and is difficult to evaporate / volatilize relative to the first solvent. Therefore, when the first solvent is completely removed, the polymer segments begin to arrange and form a completely interconnected network with the second solvent, so that the formed primary film has the ability of secondary molding. When the second solvent is removed, a completely through three-dimensional structure will be left in the film. This structure is conducive to the diffusion and conduction of the electrolyte in the film, reducing resistance. In the stage of removing the first solvent in the liquid film, the concentration of the surface polymer increases to form a relatively dense upper surface, and the surface tension of the second solvent is greater than that of the first solvent. The surface tension difference formed makes the second solvent still interact with most of the polymers due to its higher surface tension during the first solvent removal process, so that the dense skin formed by the first solvent is very thin; the dense upper surface hinders the further diffusion of the second solvent from the bottom layer through the dense layer to the solvent bath, and also hinders the penetration of the solvent bath into the primary membrane; as the upper layer of the membrane gradually solidifies, the internal solvent will diffuse into the solvent bath through the lower surface, and the lean phase will gather at the bottom to form large pores. The resulting composite polymer porous membrane has an upper surface with a dense and small-pore thin skin (also called a "dense layer") and an open large-pore lower surface. The upper surface of the thin skin can effectively avoid gas cross-over and improve its safety as a diaphragm. The open large-pore lower surface makes the composite polymer porous membrane have good electrolyte wettability and reduces resistance.

[0037] Based on the aforementioned strategy of solvent removal in steps, as the preferred technical solution of the present invention, the amount of the first solvent and the second solvent has a regulating effect on the surface and internal structure of the composite polymer porous membrane. Taking the total amount of solvent (first solvent + second solvent) as 100%, the content of the first solvent is 50%-90%, and the surface tension of the second solvent is greater than the surface tension of the first solvent. Therefore, in the first solvent removal stage, the second solvent still interacts with most of the polymers in the casting solution, so the polymer-rich phase produced by phase separation during the first solvent removal process is relatively small, so the dense cortex formed on the upper surface is very thin (also called "upper surface dense layer"), the thickness of the upper surface dense layer is 0.1-1μm, and the pore size is ≤100nm, thereby effectively avoiding gas crossover and better exerting the gas isolation effect.

[0038] Furthermore, in the process of removing the first solvent, the liquid film forms a thermodynamically unstable system and phase separation occurs, forming a polymer-rich phase and a polymer-poor phase. In the second solvent removal stage, the remaining polymer begins to phase separate to form a three-dimensional porous layer; therefore, changing the content of the second solvent has a regulatory effect on the size of the three-dimensional through-hole structure inside the composite polymer porous membrane. When the total amount of solvent is 100%, when the content of the second solvent is 10%-30%, the small droplets of the poor phase are relatively small, so when the small droplets of the rich phase solidify, the large droplets formed by the aggregation of the small droplets of the poor phase are relatively small, and the micropores of the composite polymer porous membrane are relatively small, for example, the pore size of the upper surface is 0.1-0.3μm, and the pore size of the lower surface is 0.5-0.7μm. When the content of the second solvent is 30%-50%, there are relatively more small droplets of the lean phase, so when the small droplets of the rich phase solidify, the large droplets formed by the aggregation of the small droplets of the lean phase are relatively large, and the micropores of the composite polymer porous membrane are relatively large, for example, the pore size of the upper surface is 0.3-0.5μm, and the pore size of the lower surface is 0.7-1μm. That is, by controlling the content ratio of the second solvent in the solvent (first solvent + second solvent), the microporous structure and size of the composite polymer porous membrane can be regulated.

[0039] Preferably, based on the total mass of the first solvent, the second solvent and the polymer as 100%, the mass of the polymer is 12%-30%, for example, it can be 13%, 15%, 17%, 18%, 19%, 20%, 22%, 25% or 28%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0040] As a preferred technical solution of the present invention, the first solvent, the second solvent and the polymer are first mixed to prepare a polymer solution, and then the hydrophilic inorganic particles are dispersed in the polymer solution to obtain a casting solution. The mass percentage of the polymer in the polymer solution is 12%-30%, which can make the casting solution have a suitable viscosity, which is conducive to the formation of the composite polymer porous membrane; on the other hand, the suitable content of the polymer can inhibit the dissolution of the hydrophilic inorganic particles in the membrane.

[0041] Preferably, the hydrophilic inorganic particles include any one of aluminum oxide, zirconium oxide, silicon oxide, zinc oxide, cerium oxide, barium sulfate, and magnesium hydroxide, or a combination of at least two thereof.

[0042] Preferably, the primary particle size of the hydrophilic inorganic particles is 30-200 nm, for example, it can be 40 nm, 50 nm, 70 nm, 90 nm, 110 nm, 120 nm, 140 nm, 150 nm, 160 nm or 180 nm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0043] Preferably, the mass ratio of the hydrophilic inorganic particles to the polymer is (3-7):1, for example, it can be 3.2:1, 3.5:1, 3.8:1, 4:1, 4.2:1, 4.5:1, 4.8:1, 5:1, 5.2:1, 5.5:1, 5.8:1, 6:1, 6.2:1, 6.5:1 or 6.8:1, etc.

[0044] Since the polymer has a certain hydrophobic effect, the electrolyte has a certain obstacle to the infiltration of the inside of the membrane, causing the membrane resistance to increase and the gas barrier to deteriorate, and at the same time, it makes it easy for hydrophobic substances to accumulate on the surface of the membrane, causing pollution on its surface. The present invention adds hydrophilic inorganic particles to the casting liquid, which can change the structure of the membrane and the distribution of pores, and effectively improve the hydrophilicity of the membrane. Since the preparation method of the present invention can make the inside of the composite polymer porous membrane have a high specific surface area, the hydrophilic inorganic particles are evenly loaded and not easy to fall off, and the amount of hydrophilic inorganic particles added is reduced under the premise of ensuring hydrophilicity, thereby greatly reducing costs.

[0045] Preferably, the method for preparing the casting solution specifically comprises: mixing a first solvent, a second solvent and a polymer to obtain a polymer solution; and dispersing the hydrophilic inorganic particles in the polymer solution to obtain the casting solution.

[0046] Preferably, the coating method includes roller coating, blade coating, dipping or casting. The coating method can produce a uniform and smooth liquid film with adjustable thickness, and the uniform and smooth liquid film can remove the first solvent more thoroughly, so that the final composite polymer porous film is flat, uniform and free of convex spots.

[0047] Preferably, the support mesh is immersed in the casting solution in a continuous form of winding and unwinding with tension.

[0048] Preferably, the support mesh is a porous support mesh, and the material thereof includes any one of polyphenylene sulfide, polypropylene, polyetheretherketone, and polytetrafluoroethylene, or a combination of at least two thereof.

[0049] As a preferred technical solution of the present invention, the introduction of the support net can improve the mechanical properties and strength of the composite polymer porous membrane; specifically, it can prevent the composite polymer porous membrane from being cut, broken or stretched due to mechanical stress. In addition, in a structure in which a polymer-hydrophilic inorganic particle porous membrane is provided on both sides of the support net, even if damage or holes (pinholes, etc.) are generated on one side of the support net, the gas barrier property can be ensured by the porous membrane provided on the other side of the porous support. In a structure in which a porous membrane is symmetrically provided (deposited) on both sides of the support net, the curling of the membrane can be effectively prevented, and the handling property during transportation or when the membrane is provided is further improved.

[0050] Preferably, the method of removing the first solvent in the liquid film comprises drying.

[0051] Preferably, the drying temperature is 30-120°C, for example, it can be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or 110°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific point values ​​included in the range. It is further preferred to be 45-90°C, and even more preferred to be 55-80°C.

[0052] Preferably, the drying time is 0.1-1h, for example, it can be 0.2h, 0.3h, 0.4h, 0.5h, 0.6h, 0.7h, 0.8h or 0.9h, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0053] Preferably, the method of removing the second solvent in the primary membrane comprises performing solvent replacement in a solvent bath.

[0054] Preferably, the solvent of the solvent bath includes water and / or an alcohol solvent, and more preferably any one of water, ethanol, isopropanol, n-propanol, tert-butanol, or a combination of at least two thereof.

[0055] Preferably, the temperature of the solvent replacement is 5-60°C, for example, it can be 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C or 55°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0056] Preferably, the solvent replacement time is 0.3-3h, for example, it can be 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h or 2.8h, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0057] Preferably, the solvent replacement further includes a drying step.

[0058] Preferably, the drying temperature after solvent replacement is 40-60°C, for example, it can be 42°C, 45°C, 48°C, 50°C, 52°C, 55°C or 58°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0059] Preferably, the drying time after the solvent replacement is 0.1-1h, for example, it can be 0.2h, 0.3h, 0.4h, 0.5h, 0.6h, 0.7h, 0.8h or 0.9h, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0060] Preferably, the preparation method specifically comprises:

[0061] Mixing the first solvent, the second solvent and the polymer to obtain a polymer solution; the mass percentage of the polymer in the polymer solution is 12%-30%;

[0062] The first solvent is a good solvent for the polymer, has a boiling point of T1, a surface tension of R1, and includes any one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, toluene, dichloromethane, dioxane, acetonitrile, n-pentane, and n-hexane, or a combination of at least two thereof;

[0063] The second solvent is a solvent miscible with the first solvent, has a boiling point of T2, a surface tension of R2, and includes any one or a combination of at least two of N-methylpyrrolidone, sulfolane, ethylene glycol, triethyl phosphate, trimethyl phosphate, glycerol, and dibutyl phthalate; T2-T1≥40°C, R2-R1≥5dyne / cm;

[0064] Taking the total mass of the first solvent and the second solvent as 100%, the mass of the first solvent is 50%-90%;

[0065] Dispersing hydrophilic inorganic particles in the polymer solution to obtain a casting solution; the mass ratio of the hydrophilic inorganic particles to the polymer is (3-7):1;

[0066] Applying the casting liquid on a support mesh to obtain a liquid film including the support mesh;

[0067] Drying the liquid film at 30-120° C. for 0.1-1 h to remove the first solvent to obtain a primary film;

[0068] placing the primary membrane in a solvent bath, performing solvent replacement at 5-60° C. for 0.3-3 hours, removing the second solvent, and obtaining a composite polymer porous membrane;

[0069] The solvent of the solvent bath includes any one of water, ethanol, isopropanol, n-propanol, and tert-butanol, or a combination of at least two of them.

[0070] In a second aspect, the present invention provides a composite polymer porous membrane, wherein the composite polymer porous membrane is prepared by the preparation method described in the first aspect.

[0071] Preferably, the composite polymer porous membrane has a thickness of 0.1-0.8 mm, more preferably 0.3-0.7 mm, and even more preferably 0.4-0.6 mm.

[0072] Preferably, the porosity of the composite polymer porous membrane is >60%, more preferably ≥70%, and even more preferably 80%-95%.

[0073] Preferably, the composite polymer porous membrane includes a single-sided dense surface layer (upper surface dense layer) and a single-sided open porous structure, wherein the upper surface is relatively dense and has a smaller pore size, the lower surface is relatively porous and has a larger pore size, and has an open large pore size. The interior of the composite polymer porous membrane is a three-dimensional dendritic through-hole structure.

[0074] Preferably, the pore size of the upper surface dense layer of the composite polymer porous membrane is ≤100 nm, the thickness of the upper surface dense layer is 0.1-1 μm, and the pore size of the lower surface porous layer is 0.5-2 μm.

[0075] Preferably, the surface resistance of the composite polymer porous membrane is less than 0.4Ω / cm 2 , more preferably ≤0.3Ω / cm 2 , and further preferably ≤0.28Ω / cm 2 , for example, it can be 0.19-0.28Ω / cm 2 ; The test conditions for the surface resistance are 30°C and 30wt% KOH solution.

[0076] Preferably, the bubble point pressure of the composite polymer porous membrane is greater than 1.5 bar, more preferably greater than or equal to 2 bar, for example, it may be 2-3 bar.

[0077] Preferably, the tensile strength of the composite polymer porous membrane is ≥25 MPa, more preferably 25-30 MPa.

[0078] In a third aspect, the present invention provides an application of the composite polymer porous membrane as described in the second aspect, wherein the composite polymer porous membrane is applied to an electrolytic cell diaphragm.

[0079] Preferably, the composite polymer porous membrane is applied to alkaline water electrolyzer diaphragm.

[0080] In a fourth aspect, the present invention provides an alkaline water electrolyzer, comprising a cathode, an anode and a diaphragm disposed between the cathode and the anode, wherein the diaphragm is the composite polymer porous membrane as described in the second aspect.

[0081] Compared with the prior art, the present invention has the following beneficial effects:

[0082] (1) In the preparation method provided by the present invention, a specific first solvent and a second solvent with different boiling points and surface tensions are used to prepare a casting solution, and then a composite polymer porous membrane is obtained by removing the first solvent and the second solvent in stages. Through the design and mutual coordination of solvents and processes, a composite polymer porous membrane with excellent comprehensive performance is obtained. The composite polymer porous membrane has a three-dimensional through-pore structure with high porosity and large specific surface area, so that the hydrophilic inorganic particles are evenly loaded and not easy to fall off, and has an upper surface with a dense small-pore thin skin and an open large-pore lower surface, which gives the composite polymer porous membrane excellent hydrophilicity, electrolyte wettability and conductivity, high mass transfer efficiency, good gas isolation effect, high mechanical properties and low resistance.

[0083] (2) The composite polymer porous membrane can fully meet the performance requirements of the alkaline water electrolyzer for the diaphragm. Its internal high-porosity three-dimensional through-hole structure can promote the conduction of the electrolyte between the positive and negative electrodes, thereby reducing the diaphragm resistance. The surface resistance in 30°C, 30wt% KOH solution is ≤0.28Ω / cm 2 , at a current density of 500mA / cm 2 The cell voltage is less than 1.9V, which is of great significance for reducing the system energy consumption of the alkaline water electrolyzer. At the same time, the upper surface of the composite polymer porous membrane has a dense small-pore thin skin layer, which gives it an excellent gas barrier effect, and the bubble point pressure is ≥2bar, which is conducive to avoiding the crossover of hydrogen and oxygen, making the gas high in purity, safe and reliable; and has excellent mechanical properties, with a tensile strength of ≥25MPa.

[0084] (3) The preparation method of the present invention is simple and efficient, and can conveniently and quickly obtain a composite polymer porous membrane with excellent comprehensive performance, and has broad prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0085] Figure 1 A cross-sectional SEM image of the composite polymer porous membrane provided in Example 1;

[0086] Figure 2 The SEM image of the upper surface of the composite polymer porous membrane provided in Example 1;

[0087] Figure 3 The SEM image of the lower surface of the composite polymer porous membrane provided in Example 1;

[0088] Figure 4 A cross-sectional SEM image of the composite polymer porous membrane provided in Comparative Example 1;

[0089] Figure 5 A cross-sectional SEM image of the composite polymer porous membrane provided in Comparative Example 2;

[0090] Figure 6The SEM image of the upper surface of the composite polymer porous membrane provided in Comparative Example 2;

[0091] Figure 7 This is a SEM image of the lower surface of the composite polymer porous membrane provided in Comparative Example 2. DETAILED DESCRIPTION

[0092] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0093] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0094] In the present invention, the features defined as "first" or "second" may include one or more of the features explicitly or implicitly, and are used to distinguish and describe the features, without distinction of order or importance. In the description of the present invention, unless otherwise specified, "plurality" means two or more.

[0095] The present invention is described in more detail below based on the examples, but it cannot be said that the present invention is limited to these examples. In the following examples of the present invention, the polymers, support nets, solvents and hydrophilic inorganic particles used are all commercially available products. Specifically, polysulfone, purchased from Shanghai Xunyang New Materials Co., Ltd., model S3110; polyethersulfone, purchased from Xindegao Plastic Technology Co., Ltd., model E2010; polyetheretherketone, purchased from Guangdong Zhenghao New Materials Technology Co., Ltd., model A2000; polybenzimidazole, purchased from Shanghai Shengjun Plastic Technology Co., Ltd. Polyphenylene sulfide support net, purchased from Toray of Japan; polypropylene support net, purchased from Shandong Louis New Materials Co., Ltd.; polytetrafluoroethylene support net, purchased from Shandong Louis New Materials Co., Ltd.

[0096] Example 1

[0097] A composite polymer porous membrane and a preparation method thereof, the preparation method specifically comprising the following steps:

[0098] (1) Preparation of casting solution: Dissolve polysulfone in a mixed solvent of N,N-dimethylformamide and N-methylpyrrolidone, stir evenly, and obtain a polymer solution; the mass percentage of polysulfone in the polymer solution is 12%, and the mass percentage of N,N-dimethylformamide and N-methylpyrrolidone in the mixed solvent is 50% each. Add hydrophilic inorganic particles (ZrO2, primary particle size is 50nm) to the polymer solution, wherein the mass ratio of ZrO2 to polysulfone is 3:1, stir for 24h, and perform degassing for 2h, to obtain a uniformly dispersed milky white casting solution;

[0099] (2) Preparation of liquid film: pouring the casting liquid obtained in step (1) onto a clean and ultra-flat substrate, adjusting the distance between the scraper and the glass plate on the scraping machine to scrape the casting liquid until it is flat, unwinding the polyphenylene sulfide support mesh roll and placing it on the casting liquid, and allowing it to stand so that the casting liquid is fully infiltrated between the fibers of the polyphenylene sulfide support mesh, thereby obtaining a liquid film containing the support mesh;

[0100] (3) Removing the first solvent (N,N-dimethylformamide): drying the liquid film obtained in step (2) at 80° C. for 0.2 h, thereby removing the first solvent and obtaining a primary film;

[0101] (4) Removing the second solvent (N-methylpyrrolidone): Immerse the primary membrane obtained in step (3) in deionized water at 20°C for solvent replacement. After it is completely solidified, peel it off from the substrate and continue to immerse it in a new deionized water bath until the water phase is clear and transparent, thereby completely removing the second solvent. After taking it out and drying it, the composite polymer porous membrane is obtained.

[0102] The microscopic morphology of the composite polymer porous membrane was tested by a scanning electron microscope (SEM, Regulus 8100, Hitachi, Japan). The cross-sectional SEM image of the composite polymer porous membrane provided in this embodiment is shown in FIG. Figure 1 As shown, the upper surface SEM image is as follows Figure 2 As shown, the SEM image of the lower surface is Figure 3 As shown; combined with the above three SEM images, it can be seen that the pore size and porosity of the lower surface of the composite polymer porous membrane are generally larger than those of the upper surface.

[0103] Example 2

[0104] A composite polymer porous membrane and a preparation method thereof, which differs from Example 1 only in that the components of the casting solution are different, specifically as follows: polyethersulfone is dissolved in a mixed solvent of N,N-dimethylacetamide and cyclopentane sulfone, and stirred evenly to obtain a polymer solution; the mass percentage of polyethersulfone in the polymer solution is 18%, the mass percentage of N,N-dimethylacetamide in the mixed solvent is 65%, and the mass percentage of cyclopentane sulfone is 35%. Hydrophilic inorganic particles (magnesium hydroxide, primary particle size of 80nm) are added to the polymer solution, wherein the mass ratio of magnesium hydroxide to polyethersulfone is 4:1, and the particles are evenly dispersed to obtain a casting solution; the other steps and process parameters are the same as those in Example 1 to obtain a composite polymer porous membrane.

[0105] Example 3

[0106] A composite polymer porous membrane and a preparation method thereof, which differs from Example 1 only in that the components of the casting solution are different, specifically as follows: polyetheretherketone is dissolved in a mixed solvent of acetonitrile and triethyl phosphate, and stirred evenly to obtain a polymer solution; the mass percentage of polyetheretherketone in the polymer solution is 25%, the mass percentage of acetonitrile in the mixed solvent is 75%, and the mass percentage of triethyl phosphate is 25%. Hydrophilic inorganic particles (aluminum oxide, primary particle size of 100nm) are added to the polymer solution, wherein the mass ratio of aluminum oxide to polyetheretherketone is 5:1, and the particles are evenly dispersed to obtain a casting solution; the other steps and process parameters are the same as those in Example 1 to obtain a composite polymer porous membrane.

[0107] Example 4

[0108] A composite polymer porous membrane and a preparation method thereof, which differs from Example 1 only in that the components of the casting solution are different, specifically as follows: polybenzimidazole is dissolved in a mixed solvent of dichloromethane and trimethyl phosphate, and stirred evenly to obtain a polymer solution; the mass percentage of polybenzimidazole in the polymer solution is 30%, the mass percentage of dichloromethane in the mixed solvent is 85%, and the mass percentage of trimethyl phosphate is 15%. Hydrophilic inorganic particles (zinc oxide, primary particle size of 200nm) are added to the polymer solution, wherein the mass ratio of zinc oxide to polybenzimidazole is 7:1, and the particles are evenly dispersed to obtain a casting solution; the other steps and process parameters are the same as those in Example 1 to obtain a composite polymer porous membrane.

[0109] Example 5

[0110] A composite polymer porous membrane and a preparation method thereof, the preparation method specifically comprising the following steps:

[0111] (1) Preparation of casting solution: The casting solution was prepared by using the same components and method as in Example 1;

[0112] (2) Preparation of liquid film: The casting liquid is evenly coated on both sides of the polypropylene support mesh by a double-sided roller coating method to obtain a liquid film including the support mesh;

[0113] (3) Removing the first solvent (N,N-dimethylformamide): drying the liquid film obtained in step (2) at 30° C. for 1 h to remove the first solvent and obtain a primary film;

[0114] (4) Removing the second solvent (N-methylpyrrolidone): The primary membrane obtained in step (3) is immersed in deionized water at 20°C. After it is completely solidified, it is immersed in a new deionized water bath and repeatedly immersed until the water phase is clear and transparent, thereby completely removing the second solvent. After taking out and drying, the composite polymer porous membrane is obtained.

[0115] Example 6

[0116] A composite polymer porous membrane and a preparation method thereof, the preparation method specifically comprising the following steps:

[0117] (1) Preparation of casting solution: The casting solution was prepared by using the same components and method as in Example 1;

[0118] (2) Preparation of liquid film: using a double-sided roller coating method to evenly coat the casting liquid on both sides of the polytetrafluoroethylene support mesh to obtain a liquid film containing the support mesh;

[0119] (3) Removing the first solvent (N,N-dimethylformamide): drying the liquid film obtained in step (2) at 120° C. for 0.1 h to remove the first solvent and obtain a primary film;

[0120] (4) Removing the second solvent (N-methylpyrrolidone): The primary membrane obtained in step (3) is immersed in deionized water at 20°C. After it is completely solidified, it is immersed in a new deionized water bath and repeatedly immersed until the water phase is clear and transparent, thereby completely removing the second solvent. After taking out and drying, the composite polymer porous membrane is obtained.

[0121] Example 7

[0122] A composite polymer porous membrane and a preparation method thereof, which differs from Example 1 only in that the deionized water in step (4) is replaced by anhydrous ethanol and the temperature of the solvent replacement is 5°C; other raw materials, steps and process parameters are the same as those in Example 1, and a composite polymer porous membrane is obtained.

[0123] Example 8

[0124] A composite polymer porous membrane and a preparation method thereof, which differs from Example 1 only in that the deionized water in step (4) is replaced by isopropanol and the temperature of the solvent replacement is 60°C; other raw materials, steps and process parameters are the same as those in Example 1, and a composite polymer porous membrane is obtained.

[0125] Example 9

[0126] A composite polymer porous membrane and a preparation method thereof, which differs from Example 1 only in that the deionized water in step (4) is replaced by a mixed solvent of deionized water and isopropanol in a volume ratio of 3:1, and the temperature of the solvent replacement is 40°C; other raw materials, steps and process parameters are the same as those in Example 1, and a composite polymer porous membrane is obtained.

[0127] Example 10

[0128] A composite polymer porous membrane and a preparation method thereof, which differs from Example 1 only in that the components of the casting solution are different, specifically as follows: polysulfone is dissolved in a mixed solvent of N,N-dimethylformamide and N-methylpyrrolidone, and stirred evenly to obtain a polymer solution; the mass percentage of polysulfone in the polymer solution is 12%, the mass percentage of N,N-dimethylformamide in the mixed solvent is 45%, and the mass percentage of N-methylpyrrolidone is 55%. Hydrophilic inorganic particles (ZrO2, primary particle size is 50nm) are added to the polymer solution, wherein the mass ratio of ZrO2 to polysulfone is 3:1, and the mixture is evenly dispersed to obtain a casting solution; the other steps and process parameters are the same as those in Example 1 to obtain a composite polymer porous membrane.

[0129] Embodiment 11

[0130] A composite polymer porous membrane and a preparation method thereof, which differs from Example 1 only in that the components of the casting solution are different, specifically as follows: polysulfone is dissolved in a mixed solvent of N,N-dimethylformamide and N-methylpyrrolidone, and stirred evenly to obtain a polymer solution; the mass percentage of polysulfone in the polymer solution is 12%, the mass percentage of N,N-dimethylformamide in the mixed solvent is 92%, and the mass percentage of N-methylpyrrolidone is 8%. Hydrophilic inorganic particles (ZrO2, primary particle size is 50nm) are added to the polymer solution, wherein the mass ratio of ZrO2 to polysulfone is 3:1, and the mixture is evenly dispersed to obtain a casting solution; the other steps and process parameters are the same as those in Example 1 to obtain a composite polymer porous membrane.

[0131] Example 12

[0132] A composite polymer porous membrane and a preparation method thereof, which differs from Example 1 only in that the components of the casting solution are different, specifically as follows: polysulfone is dissolved in a mixed solvent of N,N-dimethylformamide and 1,2-propylene glycol, and stirred evenly to obtain a polymer solution; the mass percentage of polysulfone in the polymer solution is 12%, and the mass percentage of N,N-dimethylformamide and 1,2-propylene glycol in the mixed solvent is 50% respectively. Hydrophilic inorganic particles (ZrO2, primary particle size is 50nm) are added to the polymer solution, wherein the mass ratio of ZrO2 to polysulfone is 3:1, and the particles are evenly dispersed to obtain a casting solution; the other steps and process parameters are the same as those in Example 1 to obtain a composite polymer porous membrane.

[0133] Embodiment 13

[0134] A composite polymer porous membrane and a preparation method thereof, the preparation method specifically comprising the following steps:

[0135] (1) Preparation of casting solution: Dissolve polysulfone in a mixed solvent of N,N-dimethylformamide and dodecanethiol, stir evenly, and obtain a polymer solution; the mass percentage of polysulfone in the polymer solution is 12%, and the mass percentage of N,N-dimethylformamide and dodecanethiol in the mixed solvent is 50% each. Add hydrophilic inorganic particles (ZrO2, primary particle size is 50nm) to the polymer solution, wherein the mass ratio of ZrO2 to polysulfone is 3:1, stir for 24h, and perform degassing for 2h, and a uniformly dispersed milky white casting solution can be obtained;

[0136] (2) Preparation of liquid film: pouring the casting liquid obtained in step (1) onto a clean and ultra-flat substrate, adjusting the distance between the scraper and the glass plate on the scraping machine to scrape the casting liquid until it is flat, unwinding the polyphenylene sulfide support mesh roll and placing it on the casting liquid, and allowing it to stand so that the casting liquid is fully infiltrated between the fibers of the polyphenylene sulfide support mesh, thereby obtaining a liquid film containing the support mesh;

[0137] (3) Removing the first solvent (N,N-dimethylformamide): drying the liquid film obtained in step (2) at 80° C. for 0.2 h, thereby removing the first solvent and obtaining a primary film;

[0138] (4) Removing the second solvent (dodecyl mercaptan): The primary membrane obtained in step (3) is immersed in methanol at 20°C for solvent replacement. After it is completely solidified, it is peeled off from the substrate and immersed in a new deionized water bath repeatedly until the water phase is clear and transparent, thereby completely removing the second solvent. After taking out and drying, the composite polymer porous membrane is obtained.

[0139] Comparative Example 1

[0140] A composite polymer porous membrane and a preparation method thereof, the preparation method specifically comprising the following steps:

[0141] (1) Dissolve polysulfone in N,N-dimethylformamide and stir to obtain a polymer solution; the mass percentage of polysulfone in the polymer solution is 12%. Add hydrophilic inorganic particles (ZrO2, primary particle size is 50nm) to the polymer solution, wherein the mass ratio of ZrO2 to polysulfone is 3:1, stir for 24 hours, and perform degassing for 2 hours to obtain a uniformly dispersed milky white casting solution;

[0142] (2) pouring the casting liquid obtained in step (1) onto a clean and ultra-flat substrate, adjusting the distance between the scraper on the scraping machine and the glass plate to scrape the casting liquid until it is flat, unwinding the polyphenylene sulfide support mesh roll and placing it on the casting liquid, and allowing it to stand so that the casting liquid is fully infiltrated between the fibers of the polyphenylene sulfide support mesh, thereby obtaining a liquid film containing the support mesh;

[0143] (3) Drying the liquid film obtained in step (2) at 80° C. for 0.2 h to remove N,N-dimethylformamide and obtain the composite polymer porous membrane.

[0144] The cross-sectional SEM image of the composite polymer porous membrane provided in Comparative Example 1 is as follows: Figure 4 As shown, Figure 3 Compared with Example 1 shown, the porosity of the composite polymer porous membrane of Comparative Example 1 is significantly reduced.

[0145] Comparative Example 2

[0146] A composite polymer porous membrane and a preparation method thereof, which differs from Example 1 only in that the drying step of step (3) is not performed, that is, the liquid membrane containing the support network obtained in step (2) is directly immersed in deionized water at 20°C for solvent replacement to obtain a composite polymer porous membrane.

[0147] The cross-sectional SEM image of the composite polymer porous membrane provided in Comparative Example 2 is as follows: Figure 5 As shown, the upper surface SEM image is as follows Figure 6 As shown, the SEM image of the lower surface is Figure 7 As shown, compared with Example 1, the porosity of the composite polymer porous membrane of Comparative Example 2 is reduced, and the upper and lower surfaces are both relatively dense and cracked structures, which is not conducive to the conduction of the electrolyte and cannot effectively isolate the gas.

[0148] Comparative Example 3

[0149] A composite polymer porous membrane and a preparation method thereof, which differs from Example 1 only in that the components of the casting solution are different, specifically as follows: polysulfone is dissolved in an N,N-dimethylformamide solvent, and then a porogen polyvinyl pyrrolidone is added thereto, and stirred evenly to obtain a polymer solution; the mass percentage of polysulfone in the polymer solution is 15%, the mass percentage of N,N-dimethylformamide is 80%, and the mass percentage of polyvinyl pyrrolidone is 5%. Hydrophilic inorganic particles (ZrO2, primary particle size is 50nm) are added to the polymer solution, wherein the mass ratio of ZrO2 to polysulfone is 3:1, and the mixture is evenly dispersed to obtain a casting solution; the other steps and process parameters are the same as those in Comparative Example 2, and a composite polymer porous membrane is obtained.

[0150] The performance test of the composite polymer porous membrane provided in Examples 1-13 and Comparative Examples 1-3 was carried out, and the specific method is as follows:

[0151] (1) Thickness: Tested according to the method in GB / T 6672-2001.

[0152] (2) Porosity: Porosity (%) = (weight of wet film - weight of dry film) / density of water / volume of wet film × 100%; wherein, the weight of wet film is the weight obtained by immersing the dry film in water for 24 hours.

[0153] (3) Surface resistance: tested according to the method in standard SJ / T10171.5-1991, the test environment is 30°C, 30wt% KOH solution, and the test area is 4cm 2 .

[0154] (4) Bubble point pressure: tested according to the method in standard GB / T 32361-2015, using Porolux TM 1000.

[0155] (5) Tensile strength: tested according to the method in standard GB / T 1040-79.

[0156] (6) Cell voltage: A single-chamber electrolytic cell with zero gap structure was constructed by using nickel foam gas diffusion layer and titanium bipolar plate. Raney nickel was used as cathode and anode catalyst. The current was provided by a DC power supply at 500 mA / cm2 under the conditions of 80 °C, 30 wt% KOH solution and 50 mL / min flow rate. 2 Under current density, evaluate the cell voltage;

[0157] The test results are shown in Table 1:

[0158] Table 1

[0159]

[0160] As can be seen from the data in Table 1, the present invention can obtain a composite polymer porous membrane with excellent performance through the design of a specific type of the first solvent and the second solvent and the combination and coordination of the process of removing the first solvent and the second solvent in sections, which has a three-dimensional through-hole structure with high porosity inside, and has an upper surface with a dense small-pore thin skin layer and an open large-pore lower surface, and has excellent hydrophilicity, electrolyte wettability and conductivity, and has a high bubble point pressure, low surface resistance, and high tensile strength. As an alkaline water electrolyzer diaphragm, it can effectively reduce the cell voltage, which is of great significance to reducing the system energy consumption of the alkaline water electrolyzer. Further, by setting the type and content of the first solvent and the second solvent, and controlling the parameters of removing the first solvent and the second solvent, the structure and functional characteristics of the composite polymer porous membrane can be effectively regulated.

[0161] Specifically, the preparation methods and test data of Example 1 are compared with those of Comparative Examples 1-2. Figure 1 , Figure 4 and Figure 5 It can be seen that the composite polymer porous membrane provided by Comparative Example 1-2 has a significantly lower porosity than that of Example 1, and the surface resistance and cell voltage are also significantly higher. This is because under the same temperature conditions, the first solvent is easier to evaporate / volatize than the second solvent, and the second solvent can always exist in the primary membrane; after the first solvent evaporates for a period of time, the casting liquid will undergo phase separation to form a rich phase rich in polymer and a poor phase with less polymer, and pores will be formed in the membrane when the second solvent is removed. The casting liquid of Comparative Example 1 contains only the first solvent. Although the casting liquid can undergo phase separation, due to the lack of the second solvent, most of the polymer phase separation occurs in the first solvent removal stage, and pores cannot be formed inside the membrane. The present invention, through the design of the first solvent and the second solvent, makes the composite polymer porous membrane have a higher porosity.

[0162] From the data in Table 1 and Figure 2 , Figure 3 , Figure 6 , Figure 7It can be seen that compared with Example 1, Comparative Example 2 adopts the traditional immersion precipitation method to prepare the porous membrane, and its bubble point pressure is lower and the gas barrier performance is poor. This is because in the immersion precipitation method of Comparative Example 2, the solvent and the coagulation bath are rapidly replaced, and the rapid solvent-non-solvent exchange on the surface causes the epidermis to rupture through the creep relaxation of the polymer, and more polymer poor phase droplets will form and combine, resulting in cracks on the surface and easy gas crossing. The upper surface of the composite polymer porous membrane of Example 1 is dense small pores, and the lower surface is a completely open structure. The dense thin skin layer on the upper surface hinders the further diffusion of the second solvent from the bottom layer through the dense layer to the solvent bath, and also hinders the penetration of the solvent bath into the casting liquid; as the upper layer of the membrane gradually solidifies, the internal solvent will diffuse into the solvent bath through the bottom surface, and the poor phase will gather at the bottom to form large pores, which is conducive to the infiltration of the electrolyte and reduces the membrane resistance. The dense upper surface is conducive to the isolation of gas. The upper and lower surfaces of the porous membrane in Comparative Example 2 are both relatively dense and cracked structures, which hinder the conduction of the electrolyte and cannot isolate the gas, resulting in high surface resistance and low bubble point pressure.

[0163] Combining the preparation methods and test data of Example 1 and Comparative Example 3, it can be seen that the diaphragm made by using two solvents with different boiling points and surface tensions and removing the solvents in stages is superior in structure and performance than the traditional NIPS+porogen molding method, and is more in line with the performance requirements of water electrolysis diaphragms.

[0164] From the preparation methods and test data of Examples 1-13 and Comparative Examples 1-2, it can be seen that by adjusting the proportion of the second solvent in the mixed solvent, the volatilization temperature of the first solvent, the conditions for solvent replacement, etc., the density and porosity of the upper and lower surfaces of the porous membrane can be changed, thereby making the mechanical strength and bubble point pressure of the porous membrane higher, and effectively blocking the cross-mixing of hydrogen and oxygen during the electrolysis process, thereby effectively improving the gas purity while ensuring safety.

[0165] The applicant declares that the present invention illustrates the composite polymer porous membrane and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a composite polymer porous membrane, characterized in that: The preparation method comprises: Mixing a first solvent, a second solvent, a polymer and hydrophilic inorganic particles to obtain a casting solution; The polymer includes any one of polysulfone, polyethersulfone, polyetheretherketone, polytetrafluoroethylene, polyphenylsulfone, polybenzimidazole, and chitosan, or a combination of at least two thereof; The first solvent is a good solvent for the polymer, has a boiling point of T1, a surface tension of R1, and includes any one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, toluene, dichloromethane, dioxane, acetonitrile, n-pentane, and n-hexane, or a combination of at least two thereof; The second solvent is miscible with the first solvent, has a boiling point of T2, a surface tension of R2, and includes any one or a combination of at least two of N-methylpyrrolidone, cyclopentane, ethylene glycol, triethyl phosphate, trimethyl phosphate, glycerol, and dibutyl phthalate; T2-T1≥40°C, R2-R1≥5 dyne / cm; The total mass of the first solvent and the second solvent is 100%, and the mass of the first solvent is 50%-90%; The total mass of the first solvent, the second solvent and the polymer is 100%, and the mass of the polymer is 12%-30%; Applying the casting liquid on a support mesh to obtain a liquid film including the support mesh; removing the first solvent in the liquid film to obtain a primary film; The second solvent in the primary membrane is removed to obtain the composite polymer porous membrane.

2. The preparation method according to claim 1, characterized in that: The hydrophilic inorganic particles include any one of aluminum oxide, zirconium oxide, silicon oxide, zinc oxide, cerium oxide, barium sulfate, and magnesium hydroxide, or a combination of at least two thereof.

3. The preparation method according to claim 2, characterized in that: The primary particle size of the hydrophilic inorganic particles is 30-200 nm.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the hydrophilic inorganic particles to the polymer is (3-7):

1.

5. The preparation method according to claim 1, characterized in that: The method for preparing the casting solution specifically comprises: mixing a first solvent, a second solvent and a polymer to obtain a polymer solution; and dispersing the hydrophilic inorganic particles in the polymer solution to obtain the casting solution.

6. The preparation method according to claim 1, characterized in that: The coating method includes roller coating, blade coating, dipping or casting.

7. The preparation method according to claim 1, characterized in that: The material of the support mesh includes any one of polyphenylene sulfide, polypropylene, polyetheretherketone, and polytetrafluoroethylene, or a combination of at least two of them.

8. The preparation method according to claim 1, characterized in that: The method of removing the first solvent in the liquid film includes drying.

9. The preparation method according to claim 8, characterized in that: The drying temperature is 30-120°C.

10. The preparation method according to claim 8, characterized in that: The drying time is 0.1-1 h.

11. The preparation method according to claim 1, characterized in that: The method of removing the second solvent in the primary film includes performing solvent replacement in a solvent bath.

12. The preparation method according to claim 11, characterized in that: The solvent of the solvent bath includes water and / or an alcohol solvent.

13. The preparation method according to claim 12, characterized in that: The solvent of the solvent bath includes any one of water, ethanol, isopropanol, n-propanol, and tert-butanol, or a combination of at least two of them.

14. The preparation method according to claim 11, characterized in that: The temperature of the solvent replacement is 5-60°C.

15. The preparation method according to claim 11, characterized in that: The solvent replacement time is 0.3-3 h.

16. The preparation method according to claim 1, characterized in that: The preparation method specifically comprises: Mixing the first solvent, the second solvent and the polymer to obtain a polymer solution; the mass percentage of the polymer in the polymer solution is 12%-30%; The first solvent is a good solvent for the polymer, has a boiling point of T1, a surface tension of R1, and includes any one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, toluene, dichloromethane, dioxane, acetonitrile, n-pentane, and n-hexane, or a combination of at least two thereof; The second solvent is miscible with the first solvent, has a boiling point of T2, a surface tension of R2, and includes any one of N-methylpyrrolidone, cyclopentane, ethylene glycol, triethyl phosphate, trimethyl phosphate, propylene glycol, and dibutyl phthalate, or a combination of at least two thereof; T2-T1≥40°C, R2-R1≥5 dyne / cm; based on the total mass of the first solvent and the second solvent being 100%, the mass of the first solvent is 50%-90%; Dispersing hydrophilic inorganic particles in the polymer solution to obtain a casting solution; the mass ratio of the hydrophilic inorganic particles to the polymer is (3-7):1; Applying the casting liquid on a support mesh to obtain a liquid film including the support mesh; Drying the liquid film at 30-120° C. for 0.1-1 h to remove the first solvent to obtain a primary film; placing the primary membrane in a solvent bath, performing solvent replacement at 5-60° C. for 0.3-3 h, removing the second solvent, and obtaining a composite polymer porous membrane; The solvent of the solvent bath includes any one of water, ethanol, isopropanol, n-propanol, and tert-butanol, or a combination of at least two of them.

17. A composite polymer porous membrane, characterized in that: The composite polymer porous membrane is prepared by the preparation method according to any one of claims 1 to 16.

18. The composite polymer porous membrane according to claim 17, characterized in that: The thickness of the composite polymer porous membrane is 0.1-0.8 mm.

19. The composite polymer porous membrane according to claim 17, characterized in that: The porosity of the composite polymer porous membrane is ≥70%.

20. The composite polymer porous membrane according to claim 17, characterized in that: The pore size of the upper surface dense layer of the composite polymer porous membrane is ≤100 nm, the thickness of the upper surface dense layer is 0.1-1 μm, and the pore size of the lower surface porous layer is 0.5-2 μm.

21. The composite polymer porous membrane according to claim 17, characterized in that: The surface resistance of the composite polymer porous membrane is ≤0.28 Ω / cm 2 .

22. The composite polymer porous membrane according to claim 17, characterized in that The bubble point pressure of the composite polymer porous membrane is ≥2 bar.

23. The composite polymer porous membrane according to claim 17, characterized in that The tensile strength of the composite polymer porous membrane is ≥25 MPa.

24. Use of the composite polymer porous membrane according to any one of claims 17 to 23, characterized in that: The composite polymer porous membrane is applied to electrolytic cell diaphragm.

25. Use of the composite polymer porous membrane according to claim 24, characterized in that: The composite polymer porous membrane is applied to alkaline water electrolyzer diaphragm.

26. An alkaline water electrolyzer, characterized in that: The alkaline water electrolyzer comprises a cathode, an anode and a diaphragm disposed between the cathode and the anode, wherein the diaphragm is the composite polymer porous membrane as described in any one of claims 17 to 23.

Citation Information

Patent Citations

  • Diaphragm for alkaline water electrolysis and preparation method and application thereof

    CN115029732A

  • High temperature resistant alkaline water electrolytic cell barrier diaphragm and preparation thereof

    CN101372752A

  • Blending modified hollow polysulfone fiber film, preparation method and application thereof

    CN101711954A